Social mobility in Sweden 1954 - Carlsson, Gösta (Lund University, 1988)
The sample was drawn by means of the central population register (CPR) of Statistics Sweden. CPR contains basic demographic and social data on every individual born on the 15th of any month, any year, and irrespective of place of birth or place of residence. Thus CPR forms, in effect, a 3.3 probability sample of the entire Swedish population. From CPR were drawn all men born in any of the years 1899, 1902, 1905, and so on, down to and including 1923. Thus there are nine birth cohorts, spaced with three-year intervals. Information about occupation in the present (son's) generation was taken from CPR. The method for gathering information on occupation in the previous (father's) generation was a different one. In CPR parish of birth (if in Sweden) and date of birth is always stated. Consequently every person can be located in the copies of the parish birth registers filed in Stockholm, and in these registers the father's occupation is stated (if the father is known). Other data collected from the CPR: place of birth and current place of residence, marital status, age of the parents, and information on income based on the tax assessments.

The sample was drawn by means of the central population register (CPR) of Statistics Sweden. CPR contains basic demographic and social data on every individual born on the 15th of any month, any year, and irrespective of place of birth or place of residence. Thus CPR forms, in effect, a 3.3 probability sample of the entire Swedish population. From CPR were drawn all men born in any of the years 1899, 1902, 1905, and so on, down to and including 1923. Thus there are nine birth cohorts, spaced with three-year intervals. Information about occupation in the present (son's) generation was taken from CPR. The method for gathering information on occupation in the previous (father's) generation was a different one. In CPR parish of birth (if in Sweden) and date of birth is always stated. Consequently every person can be located in the copies of the parish birth registers filed in Stockholm, and in these registers the father's occupation is stated (if the father is known). Other data collected from the CPR: place of birth and current place of residence, marital status, age of the parents, and information on income based on the tax assessments.
Social mobilitet i Sverige 1954
Keywords: Social and occupational mobility; Social och yrkesmässig rörlighet; Social Sciences; Samhällsvetenskap; Sociology; Sociologi